2019
DOI: 10.1097/nmd.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Illness and Defense Styles in Schizophrenia

Abstract: Although the psychological denial model argues that poor insight is a result of defense mechanisms, the direct relationship between the two remains unclear. This study aimed to examine the relationship between insight into illness and defense mechanisms while considering cognitive dysfunction in schizophrenia. A total of 38 patients with schizophrenia were evaluated for level of insight (Schedule for the Assessment of Insight), defense mechanisms (Defense Style Questionnaire), neurocognitive function (Brief As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Importantly, insight enhancement alone may affect the protective mechanism of the patient, causing them to face the disease without adequate psychological preparation. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, insight enhancement alone may affect the protective mechanism of the patient, causing them to face the disease without adequate psychological preparation. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Furthermore, the unwillingness to develop insight is also a defense mechanism of patients to avoid the painful mental illness-recognizing process. 19 Improving insight regarding a disease is a crucial current clinical practice for community-dwelling schizophrenia patients. Numerous researchers have attempted to improve medication adherence by enhancing patient insight.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with our results, insight, especially that assessed with non-face-to-face scales such as the IS, might partially reflect agreeableness or the desire to be accepted by the clinician. Nonetheless, in the previous results (Ogawa et al, 2019), even the patients' insights evaluated face to face by clinicians were related to psychological defenses after adjusting for cognitive dysfunction. Thus, the effect of defense mechanisms may not be overlooked as mere method bias.…”
Section: Discussionmentioning
confidence: 75%
“…The integrative model proposed by Lysaker et al (2018) assumes that acceptance of mental illness is deeply distressing and that insight into illness is multidetermined with potential contributions from cognitive and metacognitive dysfunction, as well as psychological factors (Vohs et al, 2016). A previous study that used a multidimensional insight scale (the Schedule for Assessment of Insight [SAI]; David et al, 1992) showed that one of the dimensions of insight (awareness of illness) was associated with immature defenses, after adjusting for cognitive dysfunction (Ogawa et al, 2019). This result suggests that insight, which consists of multiple dimensions, may include some dimensions that reflect integrative aspects of cognitive and psychological defensive factors and other dimensions that do not reflect such aspects.…”
mentioning
confidence: 99%
“…Clinical course of schizophrenia is affected by several clinical factors, such as characteristics of the disorder, comorbid psychiatric disorders, and medication adherence [4]. Insight level is also a predictive factor on clinical course of schizophrenia [5].…”
Section: Introductionmentioning
confidence: 99%